Evidence for a recommended dietary allowance for vitamin C from pharmacokinetics: A comment and analysis - Young, Vernon R. (The National Academy of Sciences of the USA, 1996)
The current recommended dietary allowance (RDA) for vitamin C, as proposed by the Food and Nutrition Board/National Research Council in 1980 and reconfirmed in 1989, is 60 mg daily for nonsmoking adult males. Levine et al. [Levine, M., Conry-Cantilena, C., Wang, Y., Welch, R. W., Washko, P. W., et al. (1996) Proc. Natl. Acad. Sci. USA 93, 3704–3709], based on a study of vitamin C pharmacokinetics in seven healthy men, have now proposed that the RDA should be increased to 200 mg daily. I have examined, in brief, the experimental and conceptual bases for this new recommendation and its implications for public health and nutrition policy and programs. Using, for illustrative purposes only, data extracted from each of two recent dietary surveys of noninstitutionalized adult males living in households in the Netherlands and the United States, it is predicted that the prevalence of intakes inadequate to meet the individual’s own requirement would be about 96% or 84%, respectively, if the criteria of adequacy used for derivation of the 200 mg RDA are accepted. Depending upon the particular average requirement value for ascorbic acid that might be derived from their data, the proposal by Levine et al. would mean a desirable increase in mean intakes in these two populations by as much about 2- to 3-fold. Hence, before an action of this kind is to be recommended, an answer must be sought to the question whether current experimental data including the criteria selected (saturation kinetics) are adequate to establish a new set of requirements for vitamin C, which then carry such profound policy implications. This will require critical assessment of all of the available evidence emerging from laboratory, clinical, and epidemiological studies to determine whether it provides a sufficient rationale for accepting criteria of vitamin C adequacy such as those proposed by Levine et al. and the requirement estimates so derived.